2000
DOI: 10.1046/j.1365-2133.2000.03707.x
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-beta1 and ultraviolet A1 radiation increase production of vascular endothelial growth factor but not endothelin-1 in human dermal fibroblasts

Abstract: Background Normal and dysregulated wound healing involves fibroblast activation and angiogenesis, in which polypeptide factors such as transforming growth factor (TGF)-b, vascular endothelial growth factor (VEGF) and endothelin-1 (ET-1) play an important part. Ultraviolet (UV) A1 (365 nm) has recently received attention as a possible treatment for some dermal fibrotic disorders.Objectives The aim of this study was to evaluate the effects of TGF-b1 and UVA1 radiation, as well as that of cobalt chloride, reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 19 publications
4
18
0
Order By: Relevance
“…The expression of vascular endothelial growth factor (VEGF) gene was upregulated in a statistically significant manner in this study, what is consistent with previously published observations, where UVA was shown to induce VEGF in dermal fibroblasts [19] and keratinocyte-derived cell lines [20]. This result suggests that UVA might affect melanoma tumor angiogenesis, via enhanced VEGF expression, and this hypothesis will be studied further in a separate project.…”
Section: Discussionsupporting
confidence: 92%
“…The expression of vascular endothelial growth factor (VEGF) gene was upregulated in a statistically significant manner in this study, what is consistent with previously published observations, where UVA was shown to induce VEGF in dermal fibroblasts [19] and keratinocyte-derived cell lines [20]. This result suggests that UVA might affect melanoma tumor angiogenesis, via enhanced VEGF expression, and this hypothesis will be studied further in a separate project.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to MDA-MB-231 cells that rely on PTHrP, the bone tropism of ER-positive MCF7, ZR75-1 and T47D cells appeared to be dependent on endothelin-1 ( EDN1 ) [115, 116]. Interestingly, EDN1 gene expression is also strongly induced by TGFβ [67, 117, 118]. Thus, one might speculate that T47D bone metastases may be driven by release of TGFβ from bone matrix followed by induction of endothelin-1 in a stromal cell population, which in turn, stimulates osteoblast activity.…”
Section: Alterations Of Tgfβ Signaling In Breast Cancer-loss Of Homeomentioning
confidence: 99%
“…TGF␤1 was shown earlier to be a potent inducer of IL-6 mRNA and protein in primary human lung fibroblasts (Eickelberg et al, 1999) and of VEGF in human dermal fibroblasts (Trompezinski et al, 2000). Furthermore, tumorderived TGF␤1 induced a myofibroblast-like phenotype of primary oral fibroblasts, which, in turn, secreted significantly higher levels of HGF (Lewis et al, 2004).…”
Section: Pkc Ros and Generation Of Myofibroblastsmentioning
confidence: 99%